Excessive Intake of Longan Arillus Alters gut Homeostasis and Aggravates Colitis in Mice - Huang, Huimin; Li, Mingxing; Wang, Yi; Wu, Xiaoxiao; Shen, Jing; Xiao, Zhangang; Zhao, Yueshui; Du, Fukuan; Chen, Yu; Wu, Zhigui; Ji, Huijiao; Zhang, Chunyuan; et al. (Frontiers in Pharmacology, 2021)
Background: Longan is the fruit of Dimocarpus longan Lour. and the longan arillus has long been used in traditional Chinese medicine possessing various health benefits. However, the excessive intake of longan is found in daily life to cause “shanghuo” syndrome. “Shanghuo” has been linked to increased disease susceptibility. The present study thus aimed to investigate the toxicological outcomes after excessive longan treatment. Methods: Longan extract at a normal dosage of 4 g/kg and two excess dosages of 8 and 16 g/kg was orally administered to normal C57BL/6J mice for two weeks or to C57BL/6J mice with DSS-induced colitis. Mouse gut microbiome were analyzed by 16S rRNA sequencing. Short chain fatty acid (SCFA) contents in colonic contents were measured by GC-MS. Colon tissue was used for histopathological observation after H and E staining, detection of protein expression by western blot, analysis of gene expression by qPCR, and detection of apoptotic cells by TUNEL assay. ELISA was used for biochemical analysis in serum. Results: In normal mice, repeated longan intake at excess doses, but not the normal dose, increased infiltration of inflammatory cells, elevated serum levels of TNF-α and IL-6 and reduced production of SCFAs. In DSS-induced colitic mice, longan intake at 4 g/kg did not promote colitis in mice, while excessive longan (8 or 16 g/kg) aggravated colitis in mice, showing increased inflammation, more serious histological abnormalities, increased gut permeability, and increased epithelia injury when compared to DSS alone. Excessive longan induced a significant reduction of microbial diversity in colitic mice, accompanied with aggravated alterations of DSS-associated bacteria including the increase of Proteobacteria phylum and genera of Bacteroides, Akkermansia, Turicibacter and Escherchia-Shigella, and the decrease of norank_f__Muribaculaceae. The changed microbial compositions were accompanied with decreased SCFAs when longan was supplemented with DSS. The aggravated colon injury by excessive intake of longan in colitic mice was tightly correlated with the altered microbial communities and decreased SCFAs production. Conclusion: Excessive longan intake disturbs gut homeostasis and aggravates colitis via promoting inflammation and altering gut microbe compositions and associated metabolism in mice. Our findings warrant rational longan arillus consumption as a dietary supplement or herbal medicine.